Biophysical and immunological pathway endophenotyping of atopic dermatitis stratified for filaggrin mutations - O'Regan, Grainne (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2015)
Atopic dermatitis (AD, eczema) is a common inflammatory skin disease, driven and modified by environmental, immunological and genetic factors. It is characterized clinically by inflammatory and pruritic skin lesions and pathologically by a cutaneous and systemic TH2 cell-dominant inflammatory response, disrupted epidermal barrier function and staphylococcus aureus colonization.
Keywords: Dermatology, Ph.D.; Ph.D. Trinity College Dublin